بعض سمات التدليل الخلدوني - el Bouazzati, Bannacer (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
This article explores the methods followed by Ibn Khaldun in presenting historical events and deducing proofs from them. It also deals with his approach in reasoning, arguing and expressing ideas. This study, which is fundamentally based on a reexamination of his al-Muqaddimah, tries to evaluate the quality of the methods of argumentation present in Ibn Khaldun’s philosophical thought